AB0998 Medium and high molecular weight hyaluronic acid injected in hip joint by US-guided technique in patients with primary or secondary hip osteoarthritis: A 2 year observational study. (23rd January 2014) - De Lucia, O.; Comi, D.; Valcamonica, E.; Pisoni, L.; Murgo, A.; Paresce, E.; Chighizola, C.; Meroni, P.
Abstract : Background: Guidelines for treatment of osteoarthritis (OA) of the hip of the American College of Rheumatology provide intra-articular therapy with steroids and hyaluronic acid (HA) in addition to standard therapy. The hip joint is difficult to approach and several studies in the literature show greater safety and accuracy when the US-guided procedure is used. The HA used are different although high molecular weight (MW) HA allows smaller number of infiltrations. However, there are no data on the best administration schedule (i.e. number or intervals of infiltrations) and on the clinical characteristics of the patients in order to get the highest efficacy. Objectives: To evaluate the efficacy and safety of medium and high MWHA injection in hip joint by US-guided technique with a follow up of 2 years. To study if there are negative predictive factor for this therapy. Methods: 95 hips of 91 patients (45 M; 46 F), mean age 57, 6±15, 35, 80 primary hip OA, 15 hip OA secondary to inflammatory rheumatic diseases were randomly assigned to treatment with Hylan G-F 20 [Synvisc®-Genzyme] (56 hips), or Sodium Hyaluronate >1.6KDa [Hyalubrix®-Fidia] (39 hips), intra-articularly in the hip. The treatment consisted of three injections: at the inclusion, after 1 and 2 months; then the treatment was repeated every 6 months. Efficacy was assessed by pain evaluation on a 100mm VAS scale and WOMAC questionnaire for hip osteoarthritis recorded at the inclusion, after 1, 6, 12 and 24 months. Data on age, BMI, radiologic degree of OA (Kellgren-Lawrence scale) and duration of symptoms were also recorded at the inclusion. Viscosupplementation was performed with an anterior sagittal approach, under ultrasound guidance. Patient who had to recur to prosthesis up to six months after the end of the study were excluded. Friedman test for repeated measures with Bonferroni correction was used to test efficacy of the treatment. Multivariate logistic regression analisys was used to find if there were predictive indices for the response variables. Results: The treatment produced a significant improvement on VAS pain and on WOMAC total score (p<0.0001) rapidly after 1 month maintained over 2 years independently from radiological degree of OA, independently from the type of HA used and present both in primary and secondary OA group. The improvement was faster in the group treated with higher MW HA that was showed by a significant improvement on VAS pain (p=0.039) between T0 and T1 in the higher MW group vs. medium MW group. Multivariate logistic regression analysis on age, disease duration, BMI and radiological degree didn't showed any significance. However there was a trend towards significance that shows that patients non responder to treatment were older than average (p=0.08) and with higher BMI (p=0.09). Conclusions: With our scheme of treatment there was an improvement on pain function immediately one month after intraarticular HA treatment that was maintained over the 2 years. In our study high MW Synvisc seems to be more rapid in the effect than medium MW Hyalubrix. Advanced age and higher BMI seems to be negative predictive factors for the result of the therapy, while radiological scoring is not. Further studies with larger numbers of patients and control arms are needed to confirm our results. Disclosure of Interest: None Declared